2016
DOI: 10.18632/oncotarget.8598
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of high B7-H4 expression in patients with solid tumors: a meta-analysis

Abstract: BackgroundRecently, many studies have shown that B7-H4 exhibits altered expression in various cancers. We performed a meta-analysis to evaluate the prognostic role of B7-H4 expression in solid tumors.ResultsData from 18 observational studies and 2467 patients were summarized. An elevated baseline B7-H4 was significantly associated with worse OS (pooled HR = 1.79; 95% CI = 1.56–2.06). Differences across subgroups of tumor type, patients' ethnicity, analysis type, HR obtain method and cut-off value were not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
3
15
1
Order By: Relevance
“…Together these results demonstrate mutually exclusive expression of known negative regulators of T cells (such as PD-L1 or IDO1) which are positively correlated with presence of CD8 + T cells and the PD-L1 family member, B7-H4 which is negatively correlated with presence of CD8 + T cells. Our data thus reveals that expression of immune checkpoint targets is distinct between Although originally characterized by its expression on hematopoietic cells, elevated levels of B7-H4 on tumor cells, as was observed here, correlate with poor clinical outcome across multiple types of solid tumors (38). Consistent with our data, B7-H4 expression is upregulated by TGF-1 signaling in colorectal cancer (39).…”
Section: Discussionsupporting
confidence: 89%
“…Together these results demonstrate mutually exclusive expression of known negative regulators of T cells (such as PD-L1 or IDO1) which are positively correlated with presence of CD8 + T cells and the PD-L1 family member, B7-H4 which is negatively correlated with presence of CD8 + T cells. Our data thus reveals that expression of immune checkpoint targets is distinct between Although originally characterized by its expression on hematopoietic cells, elevated levels of B7-H4 on tumor cells, as was observed here, correlate with poor clinical outcome across multiple types of solid tumors (38). Consistent with our data, B7-H4 expression is upregulated by TGF-1 signaling in colorectal cancer (39).…”
Section: Discussionsupporting
confidence: 89%
“…However, Zang et al [ 13 ] reported that B7-H4 wasn't an independent prognostic indicator, the reason why this phenomenon appeared may rely on the limited follow-up years for the long-survival period of prostate cancer patients. The previous meta-analysis which had investigated the high expression of B7-H4 influenced the prognosis of solid tumor patients also showed this trend as we illustrated [ 29 ]. While that article only included the samples derived from the tumor tissue and only contained 18 articles.…”
Section: Discussionsupporting
confidence: 73%
“…Compared with blocking the B7 family members which express precisely on various tumor, controlling the upstream stages in turn regulating effector T cells acting on peripheral tumors seems inefficient and imprecise [ 27 ]. B7-H1 is another potential immunotherapy target which is expressed on tumor and normal tissues, but B7-H4 can hardly be discovered in normal tissue and the expression pattern in tumor is wider than B7-H1[ 28 , 29 ]. Chen et al [ 30 ] also reported that B7-H4 overexpression was correlated with pancreatic cancer patients’ OS ( P < 0.001), whereas the expression of B7-H1 didn't ( p = 0.089).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous meta-analysis investigated whether high B7-H4 expression influenced the prognosis of solid tumor patients. [ 29 ] In our study, we found that high expression of B7-H4 was an independent prognostic indicator of poor survival. However, certain limitations to our study should be considered.…”
Section: Discussionmentioning
confidence: 57%